Innovations in Oral Dispersible Tablets: Improving Bioavailability and Patient Compliance in NSAID Therapies - Pallavi Karanje (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Non-steroidal anti-inflammatory drugs (NSAIDs) are essential medications known for their analgesic, anti-inflammatory, and antipyretic properties. However, challenges such as poor solubility, variable bioavailability, and patient adherence have spurred research into innovative drug delivery systems. Oral dispersible tablets (ODTs) have emerged as a solution to address these challenges by improving drug absorption and enhancing patient compliance through convenient administration. Methods and Materials: This review consolidates information from peer-reviewed articles, clinical trials, and authoritative sources to examine recent advancements in ODT formulations for NSAID therapies. Key databases including PubMed, Scopus, and Web of Science were searched using relevant keywords such as "oral dispersible tablets," "NSAIDs," "bioavailability," and "patient compliance." Studies focusing on formulation technologies, clinical efficacy, manufacturing challenges, and regulatory considerations were included. Results Analysis: Innovations in ODT formulations have significantly enhanced drug dissolution rates, taste-masking effectiveness, and controlled release capabilities for NSAIDs. Clinical studies have demonstrated that ODTs provide rapid onset of action, improved bioavailability, and enhanced patient compliance compared to conventional tablet formulations. Challenges including stability issues, scalability of manufacturing processes, and regulatory hurdles remain critical considerations.